Quantum field methods in the electron cooling - Khelemelya, O.V.; Kholodov, R.I. (Вопросы атомной науки и техники, 2013)
Quantum field methods are proposed to describe the electron cooling process. The influence of the magnetic field and the anisotropy of the temperature distribution of the electron gas are considered in the framework of quantum field theory. It is shown the longitudinal component of the thermal motion of electrons acts the main role in the electron cooling of heavy ions in the presence of a sufficiently strong magnetic field. Quantum effects in the electron cooling are estimated. Запропоновано використовувати квантово-польовi методи для опису процесу електронного охолодження. Розглянуто в рамках квантової теорiї поля вплив магнiтного поля з урахуванням анiзотропiї температурного розподiлу електронного газу. Показано, що в присутностi сильного магнiтного поля головну роль в електронному охолодженнi важких iонiв вiдiграє повздовжня компонента теплового руху електронiв. Проведено оцiнку квантових ефектiв в електронному охолодженнi. Предложено использовать квантово-полевые методы для описания процесса электронного охлаждения. Рассмотрено в рамках квантовой теории поля влияние магнитного поля при учете анизотропии температурного распределения электронного газа. Показано,что в присутствии достаточно сильного магнитного поля главную роль в электронном охлаждении тяжелых ионов отыгрывает продольная составляющая теплового движения электронов. Проведена оценка квантовых эффектов в электронном охлаждении.